PELAKSANAAN INSTRUMEN HUKUM PUBLIK PEMERINTAHAN DESA DALAM PENINGKATAN KESEJAHTERAAN MASYARAKAT OLEH BUMDES MUARA UWAI SEJAHTERA KECAMATAN BANGKINANG KABUPATEN KAMPAR TAHUN 2018 - Yuliantika, Rani; Amin, Raja Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Law Number 6 Year 2014 Regarding Villages, emphasizes that Villages can establish BUMDes, in article 1 paragraph (6) it is mentioned that a Village Owned Enterprise, hereinafter referred to as BUM Desa is a business entity whose entire or most of the capital is owned by the Village through an equity participation. directly originating from village assets separated to manage assets, services and other businesses for the maximum welfare of the village community. The problem formulation in this research is How is the Implementation of the Village Government Public Legal Instrument in Improving Community Welfare by Muara Uwai Sejahtera BUMD Bangkinang District, Kampar Regency in 2018?This research was conducted with the aim of describing the implementation of the Village Government Public Legal Instrument in improving community welfare by BUMDes Muara Uwai Sejahtera, Bangkinang District, Kampar Regency in 2018. This research is a descriptive study with a qualitative approach. The location of this research was carried out in Muara Uwai Village. Data collection techniques used were observation, interviews and documentation. The data analysis technique used is descriptive and qualitative methods.The results of the study concluded If viewed from the types of government public legal instruments, namely policy regulations with circulars provided for delinquent customers, government plans in vision, mission mentioned economic development through BUMDes, and in the 2016-2021 RPJMDes in Muara Uwai Village already listed the establishment and development of BUMDes accompanied by funds, and seen from the 2018 RKPDes mentioned in the establishment and development of BUMDes and accompanied by a ceiling of funds. However, if seen from the regulations namely Uwai Muara Village Regulation Number 4 of 2015 concerning Establishment of BUMDes has not been implemented optimally and the Decree or decision, if seen Decision or decision relating to the management capacity of the implementation of BUMDes management especially the position of Director of BUMDes, is considered unable to develop BUMDes